The Effect of Mathematical Disposition on Basic Mathematical Abilities in the Online Learning - Setiawan, Yayan Eryk; Surahmat (Journal of Education Reseach and Evaluation, 2023)
The problem that arises from online learning is decreased learning outcomes or low ability in mathematics. This problem can be overcome by looking for various variables in online learning. Researchers suspect that this mathematical disposition influences basic mathematical abilities. Thus, the purpose of this study was to analyze the effect of mathematical disposition on basic mathematical abilities in online learning. This type of research is quantitative research with a comparative causal approach. The sample of this research is 65 prospective mathematics teacher students at the Islamic University of Malang. The research data is in the form of the results of filling out the mathematical disposition questionnaire and the results of working on basic math skills questions. The research instrument consisted of a questionnaire and questions. The questionnaire and questions used have met valid and reliable criteria. The data analysis technique used in this study is a simple correlation and regression analysis with the help of SPSS. The results showed that mathematical disposition (self-confidence, creativity, persistence, curiosity, positive values, and respect) had a positive effect on basic mathematical abilities by 14.5%. From the research results, it can be concluded that the metaphysical disposition variable is positively correlated with the mathematical basic ability variable. The results of the study also show that mathematical disposition has a positive effect on basic mathematical abilities during online learning. The important mathematical disposition components to pay attention to during online learning are creativity, persistence, curiosity, positive value, and respect for mathematics. These components are the benchmarks for the influence of mathematical disposition on basic mathematical abilities.